2011
DOI: 10.1021/jf104157z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growing Season on Phenolic Compounds and Antioxidant Properties of Grape Berries from Vines Grown in Subtropical Climate

Abstract: The influence of growing season (winter vs summer) on the synthesis and accumulation of phenolic compounds and antioxidant properties was studied in five grape cultivars for three consecutive years. Four phenolic compound parameters (total phenols, flavonoids, flavan-3-ols, and anthocyanins) and three antioxidant property parameters [2,2-diphenyl-1-picrylhydrazyl radical scavenging, 2,2-azinobis(3-ethylbenzothiazolinesulfonic acid) radical scavenging, and ferric reducing antioxidant power] were investigated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 27 publications
12
77
2
Order By: Relevance
“…In other words, the degradation of some phenols was faster or slower than the biosynthesis of other phenols. Moreover, a reversed correlation between the phenolic compounds concentration and air temperature was reported (Xu et al, 2011), similar results being observed in the current study.…”
Section: Resultssupporting
confidence: 92%
“…In other words, the degradation of some phenols was faster or slower than the biosynthesis of other phenols. Moreover, a reversed correlation between the phenolic compounds concentration and air temperature was reported (Xu et al, 2011), similar results being observed in the current study.…”
Section: Resultssupporting
confidence: 92%
“…Regarding the white varieties, Smederevka grapes were richer with TP and TF in seeds and skins, but lower amount of flavan-3-ols was found, compared to the grape varieties grown in a Subtropical Climate (Xu et al, 2011). Furthermore, the content of total phenolics in Smederevka and Chardonnay skins were similar to that found in the white Czech varieties (Lachman et al, 2009).…”
Section: Grape Varietysupporting
confidence: 59%
“…Compared to other grape varieties, Vranec grapes presented higher amounts of total phenolics in seeds and skins, higher levels of anthocyanins and lower levels of TF and TF 3-ols in seeds and skins than red "Kyoho" (Euro-American hybrid) and the Euro-Asian hybrid 'NW196' cultivars grown in Subtropical Climate (Xu, Zhang, Zhu, Huang, & Lu, 2011). In addition, Vranec skins presented a similar amount of total phenolics compared to some grape varieties grown in Czech Table 3 Content of total polyphenols, anthocyanins, flavan-3-ols and flavonoids of Vranec, Merlot, Smederevka and Chardonnay grapes at physiological maturity, determined by spectrophotometic assays, and expressed as mg/g fresh weight.…”
Section: Influence Of Varietymentioning
confidence: 82%
“…Malvidin-3,5-O-diglucoside was the most significant anthocyanin for 'NW196' grape berries (Xu et al, 2011), and the same was true for the 'NW196' wine. 'Noble' wine was very rich in Cyanidin-3,5-O-diglucoside and Pelargonidin-3,5-Odiglucoside.…”
Section: Descriptive Analysis (Da)mentioning
confidence: 76%